2015
DOI: 10.1155/2015/715859
|View full text |Cite
|
Sign up to set email alerts
|

Performance Enhancing Diets and the PRISE Protocol to Optimize Athletic Performance

Abstract: The training regimens of modern-day athletes have evolved from the sole emphasis on a single fitness component (e.g., endurance athlete or resistance/strength athlete) to an integrative, multimode approach encompassing all four of the major fitness components: resistance (R), interval sprints (I), stretching (S), and endurance (E) training. Athletes rarely, if ever, focus their training on only one mode of exercise but instead routinely engage in a multimode training program. In addition, timed-daily protein (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 371 publications
(479 reference statements)
0
20
0
Order By: Relevance
“…In addition, the impact of the dietary interventions on acid-base balance can be estimated by blood gas analysis parameters, and an increase in [HCO 3 − ] concentration and elevated pH b are both found after acid-base manipulation with ergogenic aids such as NaHCO 3 [40,41]. A few recent studies have suggested that alkalizing diets are unable to produce the same severe effect on acid-base balance and blood buffering capacity compared with alkalizing ergogenic aids [55,67]. However, the present study showed significantly increased pH b , [HCO 3 − ], and BE values for the BASE condition compared with the ACID conditions, indicating a higher alkalotic state prior to PTSR exercise testing for the BASE trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the impact of the dietary interventions on acid-base balance can be estimated by blood gas analysis parameters, and an increase in [HCO 3 − ] concentration and elevated pH b are both found after acid-base manipulation with ergogenic aids such as NaHCO 3 [40,41]. A few recent studies have suggested that alkalizing diets are unable to produce the same severe effect on acid-base balance and blood buffering capacity compared with alkalizing ergogenic aids [55,67]. However, the present study showed significantly increased pH b , [HCO 3 − ], and BE values for the BASE condition compared with the ACID conditions, indicating a higher alkalotic state prior to PTSR exercise testing for the BASE trials.…”
Section: Discussionmentioning
confidence: 99%
“…The PRAL model is based on the content of proteins, Cl − , PO4 3− , SO4 2− , Na + , K + , Ca 2+ , and Mg 2+ [52] and was calculated as follows: PRAL (mEq/100 g) = 0.49 × protein (g/100 g) + 0.037 × phosphorus (mg/100 g) − 0.021 × potassium (mg/100 g) − 0.026 × magnesium (mg/100 g) − 0.013 × calcium (mg/100 g) [56]. In general, vegetables, fruits, and potatoes have the highest alkalizing potential (low-PRAL nutrients), while meat, cheese, cereal products, and eggs promote systemic acidity (high-PRAL nutrients) [48,54,55]. In addition, a German PRAL food list published by the Institute for Prevention and Nutrition, Ismaning, Germany, [52] and suggestions for recipes were given to the participants to meet the requirements of the alkalizing or acidizing diet.…”
Section: Dietary Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beetroot juice (BRJ) contains a high concentration of nitrate (up to 11.4 g/L) as compared to drinking water (<45 mg/L in European countries) or other foods and beverages (Drinks 2019;Vermeer & van Maanen, 2001;Wruss et al 2015). As nitrate intake may enhance sports performances, the use of BRJ by athletes has been increasing over the years, especially in endurance sports (Arciero, Miller, and Ward 2015). A five percent growth each year in the global beetroot juice market has been reported, and this rise will probably continue during the upcoming years (Growing Popularity of Beetroot Juice to Fuel the Global Market for Beetroot Powder During 2017During -2027During 2017.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the distribution of macronutrients has to be planned to guarantee the availability of substrates to regulate metabolic pathways, and modulate the muscle-skeleton adaptations induced by physical training 4 , with athletes continuously monitoring and adjusting their macronutrient consumption in order to optimize their athletic performance 5,6 .…”
Section: Introductionmentioning
confidence: 99%